Nalar Hermeneutis Ulama Hadis: Larangan Perempuan Bepergian tanpa Mahram dalam Ruang Sejarah Pemahaman - Miski, Miski (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
This article explains how the construction of the hermeneutical reason of hadith scholars related to the hadith of the prophet that mentions the prohibition of women travels without a mahram. Using the sociological and historical approach, and hermeneutic analysis, the findings point to the conclusion that the hadith exists with a diverse narrative, especially related to the boundary radius of distance and travel time. To understand this hadith, scholars need to analyze further and interpret the hadith based on the context, not merely on its literal text. To conclude their interpretation, the prohibition of women travelling without their mahramsis related to comfort and safety. A mahram can either be replaced or removed when the situation is already safe. In other words, the role of a mahramis considered more on its functional instead of its existential aspect. Despite the use of hermeneutics approach by contemporary scholars to sustain the existing studies, this study still becomes a critique since the offer is not entirely new. Previous scholars have used this hermeneutic approach, and since their understanding is contextually based on their own era, diverse interpretation is inevitable.